2008
DOI: 10.1007/s11274-008-9839-7
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of bacteria producing polyhydroxyalkanoates (PHA) from municipal sewage sludge

Abstract: Bacterial isolates from sludge samples collected at a local municipal sewage treatment plant were screened for bacteria producing polyhydroxyalkanoates (PHA). Initially Sudan black B staining was performed to detect lipid cellular inclusions. Lipid-positive isolates were then grown in a nitrogen limitation E2 medium containing 2% (w/v) glucose to promote accumulation of PHA before the subsequent staining with Nile blue A. The positive isolates were quantified initially with a u.v. spectrophotometer, for a very… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(6 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…Isolate of PSA10 which is the highest PHB-producing bacterial strain, compared to both local amylolytic bacteria producing PHB (Table 1), was closely related to B. megaterium based on the analysis of 16S rRNA gene. This corresponds with the previous studies, which reported that B. megaterium is a bacteria that is known as the PHB producer who first investigated (Lenz & Marchessault 2005;Visnuvardhan et al 2008).…”
Section: Identification Of the Amylolytic Bacteria Producing Of Phb Bsupporting
confidence: 90%
See 1 more Smart Citation
“…Isolate of PSA10 which is the highest PHB-producing bacterial strain, compared to both local amylolytic bacteria producing PHB (Table 1), was closely related to B. megaterium based on the analysis of 16S rRNA gene. This corresponds with the previous studies, which reported that B. megaterium is a bacteria that is known as the PHB producer who first investigated (Lenz & Marchessault 2005;Visnuvardhan et al 2008).…”
Section: Identification Of the Amylolytic Bacteria Producing Of Phb Bsupporting
confidence: 90%
“…Species references selected in this study are Bacillus subtilis, Bacillus cereus and Bacillus megaterium. The three species were chosen because the references has been known to hydrolyze starch (Holt et al 1994) and accumulate PHB (Halami 2008;Singh et al 2009;Visnuvardhan et al 2008). In this study, Bacillus pumilus used also as a reference species to represent members of the genus Bacillus which has a different character with the three reference species selected.…”
Section: Determination Of Reference Strains By Profile Matching Methodsmentioning
confidence: 99%
“…DiVerent samples from the municipal sewage treatment plant at Hyderabad, India, were screened for PHA-producing bacteria and have been described elsewhere [9]. Bacterial strain 88D was isolated on Luria Bertani (LB) medium (Hi media, India).…”
Section: Bacterial Strainmentioning
confidence: 99%
“…Alcaligenes , which belong to the family Alcaligeneceae , was reported to have a high PHA accumulation potential (Vishnuvardhan Reddy et al . ). However, this study could not find specific PHA‐accumulating organisms that might be related to the PHA accumulation potentials observed in the PHA accumulation experiments (Figs and ).…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, only a few studies have investigated the abundance and taxonomic compositions of PHA‐accumulating bacteria in activated sludge using culture‐dependent (Vishnuvardhan Reddy et al . ) and culture‐independent molecular techniques (Oshiki et al . , ).…”
Section: Introductionmentioning
confidence: 99%